Functional Stability (at +4°C) of Hematopoietic Stem and Progenitor Cells Amplified Ex Vivo from Cord Blood CD34+ Cells. Issue 8 (August 2013) - Duchez, Pascale; Chevaleyre, Jean; De La Grange, Philippe Brunet; Vlaski, Marija; Boiron, Jean-Michel; Ivanovic, Zoran
Our previously published ex vivo expansion procedure starting from cord blood CD34 + cells enables a massive expansion of total and CD34 + cells and committed progenitors without negative impact on stem cells exhibiting both short- and long-term repopulating capacity. It was upgraded to clinical scale [Macopharma HP01 ® medium in presence of SCF, FLT3-L (100 ng/ml each), G-SCF (10 ng/ml), and TPO (20 ng/ml)] and is in use for an ongoing clinical trial (adult allogeneic context), yielding encouraging results. In order to test the possibility to use the expanded cells in distant transplantation centers, we studied the functional stability at +4°C (usual temperature of transportation) of hematopoietic progenitors and stem cells 48 h after expansion. If the cells were washed and resuspended in 4% albumin solution (actual procedure for immediate injection), only one half of total nucleated and CD34 + cells and 30% of committed progenitors survived after 24 h. This condition has also an evident negative impact on stem cells in expansion product as demonstrated on the basis of reconstitution of NSG mice bone marrow by human CD45, CD33, CD19 + cells as well as by human committed progenitors (CFU). Surprisingly, if the cells were stored 48 h at +4°C in culture medium, very good survival of total and CD34 + cells (90 to 100%) and colony forming unit cells (CFCs; around 70%) was obtained, as well as the maintenance of stem cells (the same in vivo assay with NSG mice). These data point to the possibility of the maintenance of the full functional capacity of expanded grafts for 2 days, the time allowing for its transportation to any transplantation center worldwide.